Analysis of the Effectiveness of Digital Strategy in Increasing Product Sales with the EPIC Model Approach - Rozikin Rozikin; M. Imron Mas'ud (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
This study aims to evaluate the effectiveness of digital strategy in increasing sales of hijab products at CV Age Group. This research uses market research methods to develop and implement a digital strategy focusing on social media and paid advertising campaigns without involving SEO (Search Engine Optimization) and SEM (Search Engine Marketing). Sales data was analyzed to assess the impact of this strategy on product visibility and sales performance. The results showed that the digital strategy successfully increased the visibility and sales of hijab products. Social media effectively reached a wider audience and improved customer interaction, while paid advertising increased sales. The findings of this implication confirm the effectiveness of digital strategies in marketing hijab products and the importance of strategy updates to maintain a competitive advantage.